2021
DOI: 10.1080/1828051x.2021.1904795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broussonetia papyrifera L. (paper mulberry) on growth performance, carcase traits, meat quality and immune performance in Hu ram lambs

Abstract: This study was carried out in an attempt to evaluate the impact of Broussonetia papyrifera as a roughage substitute at different levels on carcase traits, growth performance, meat quality and immune performance in Hu ram lambs. Sixty Hu rams (5 months of age, 26.70 ± 2.14 kg body weight) were randomly divided into four groups. The treatments comprised B. papyrifera supplementation at levels of 0% (G0), 30% (G30), 60% (G60) and 100% (G100) of roughage feed. The results suggested that diet supplemented with B. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…In the present study, PMS30 and PMS40 contained higher DMI and ADG than others, which was similar to the results in goats, sheep, and beef cattle fed with paper mulberry or paper mulberry silage [14,15,24]. This might be due to the replacement of low quality corn stover with high quality silage in the diets for Hu lambs, and it was also consistent with the result reported by Tao that PMS could increase the DMI in beef cattle [24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, PMS30 and PMS40 contained higher DMI and ADG than others, which was similar to the results in goats, sheep, and beef cattle fed with paper mulberry or paper mulberry silage [14,15,24]. This might be due to the replacement of low quality corn stover with high quality silage in the diets for Hu lambs, and it was also consistent with the result reported by Tao that PMS could increase the DMI in beef cattle [24].…”
Section: Discussionsupporting
confidence: 92%
“…The meat quality of Hu lamb was not affected by PMS in the present study, which is consistent with the previous study in Hu rams after being fed with paper mulberry [15]. However, the previous study showed that paper mulberry could improve the meat quality of goats compared to maize silage [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mulberry silage had good palatability. In this study, the dry matter intake and average daily gain (ADG) of lambs in the L and M groups were as good as those in the CON group, which was similar to the results in studies conducted by Sheng [ 26 ], Hua [ 27 ] and Tao [ 28 ], who used dried mulberry leaves and mulberry silage to feed sheep and beef cattle. Using mulberry silage to replace up to 60% of maize silage in the diet is an effective way to introduce a more environmentally friendly crop.…”
Section: Discussionsupporting
confidence: 89%
“…The crude protein content in the leaves of paper mulberry can reach more than 20%, which is higher than that of plants such as alfalfa (Medicago sativa, Shi S L). Research shows that using B. papyrifera as a raw material to produce feed for cattle, sheep, and pigs can greatly improve the quality of the meat and as a high-quality feed it can greatly reduce the cost of feed [19][20][21][22][23]. If it can be developed into a new type of feed material, it can not only increase the added value of paper mulberry but also reduce the cost of feed and promote the development of industry.…”
Section: Introductionmentioning
confidence: 99%